The Inhibitory Effect of the Deregulation Short-Sale on Private Equity Placement - Wang, Panna; Su, Chun; Xu, Botao (Frontiers in Psychology, 2022)
In countries with a high degree of equity concentration, such as China, the second type of agency problem is serious in which major shareholders of listed companies encroach on the interests of small and medium shareholders through private placement. As a financial transaction system, the short-selling mechanism has the function of external corporate governance. Therefore, this paper examines the impact of relaxing short-selling controls on companies’ private placements. Based on the quasi-natural experiment of China’s gradual relaxation of short-selling controls since 2010, a double-difference model (DID) test is constructed to find that relaxing short-selling controls reduces companies’ private placement tendency and amount, and this effect is mainly reflected in samples with a higher degree of equity checks and balances. Further analysis found that when the size of the company's financing constraints is different, the impact of relaxing short-selling control on the company's private placement tendency and amount is different; when the chairman and the general manager have two positions, relaxing short-selling control reduces the company's private placement options, but it has a negative impact on the company's private placement. There is no difference in the impact of the company's private placement amount. It can be excluded that the relaxation of short-selling control suppresses the company’s placement through financing constraints and corporate governance mechanisms. Compared to a good information environment, when the company's information environment is poor, relaxing short-selling controls reduces the company's private placement tendency and amount. Significantly, it shows that the relaxation of short-selling control policy and supervision inhibits the company's private placement through the information environment mechanism, and promotes the sustainable development of enterprises. It not only improves the literature in the field of short selling mechanism affecting corporate behavior, but also enriches the research on the transfer of benefits of private placement of companies.